The Ecology of Kaili Oral Literature in Narrative and Non-Narrative Form in Dolo District, Sigi Regency - Gazali Gazali; Syamsuddin Syamsuddin; Agustan Agustan; Ade Nurul Izatti; Fadillah Fadillah (JENTERA: Jurnal Kajian Sastra, 2026)
Indonesia possesses a rich tradition of oral literature that reflects local culture and indigenous wisdom, with regional languages serving as inherited cultural identities across generations. One of these traditions is the Kaili oral literature in the Ledo dialect, which is actively preserved in Dolo District, Sigi Regency, Central Sulawesi. This study aims to examine the forms and ecological meanings of Kaili oral literature, both narrative and non-narrative, and to document its role in preserving local cultural and environmental knowledge. Using a literary ecology approach, this study analyzes the relationship between culture and environment as represented in oral traditions, focusing on how human interactions with nature, social life, and spiritual beliefs are encoded in oral expressions. The data were analyzed qualitatively to identify linguistic forms, symbolic meanings, and ecological values embedded in legends, myths, customary expressions, poems, and folk songs. The findings show that Kaili oral literature comprises narrative forms (legends and myths) and non-narrative forms (customary expressions, poetry, and folk songs), all of which embody ecological values such as environmental ethics, respect for nature, social harmony, and spiritual balance. Narrative texts emphasize human–nature–spiritual relationships through symbolic events, while non-narrative texts function as moral guidance, social regulation, and ecological awareness in daily life. Kaili oral literature serves not only as cultural heritage but also as a medium of ecological education that reinforces the interconnectedness between humans and the environment. Abstrak Indonesia memiliki kekayaan tradisi sastra lisan yang mencerminkan budaya dan kearifan lokal, dengan bahasa daerah sebagai identitas budaya yang diwariskan secara turun-temurun. Salah satu di antaranya adalah sastra lisan Kaili dialek Ledo yang berkembang di Kecamatan Dolo, Kabupaten Sigi, Sulawesi Tengah. Penelitian ini bertujuan untuk mengkaji bentuk dan makna ekologis sastra lisan Kaili, baik dalam bentuk naratif maupun non-naratif, serta mendokumentasikan perannya dalam pelestarian pengetahuan budaya dan lingkungan masyarakat lokal. Penelitian ini menggunakan pendekatan ekologi sastra untuk menganalisis hubungan antara budaya dan lingkungan sebagaimana tercermin dalam tradisi lisan. Analisis difokuskan pada bentuk linguistik, makna simbolik, serta nilai-nilai ekologis yang terkandung dalam legenda, mitos, ungkapan adat, syair, dan nyanyian rakyat. Data dianalisis secara kualitatif untuk mengidentifikasi pola representasi hubungan manusia dengan alam, sosial, dan spiritual dalam tradisi lisan Kaili. Hasil penelitian menunjukkan bahwa sastra lisan Kaili terdiri atas bentuk naratif (legenda dan mitos) serta non-naratif (ungkapan adat, syair, dan nyanyian rakyat) yang sama-sama mengandung nilai ekologi. Sastra lisan naratif menekankan relasi manusia, alam, dan spiritual melalui simbolisasi peristiwa dan tokoh, sedangkan sastra lisan non-naratif berfungsi sebagai media pendidikan moral, pengendalian sosial, dan penanaman kesadaran ekologis dalam kehidupan sehari-hari. Sastra lisan Kaili tidak hanya berfungsi sebagai warisan budaya, tetapi juga sebagai media pendidikan ekologis yang menegaskan keterhubungan manusia dengan lingkungan dan semesta.